A Heating and Cooling Stage With Fast Temporal Control for Biological Applications - Manon Valet; Juan M. Iglesias-Artola; Falk Elsner; Anatol W. Fritsch; Otger Campas (IEEE Open Journal of Engineering in Medicine and Biology)
The study of biological processes involving live microscopy techniques requires adequate temperature control to respect the physiology of the organism under study. We present here a design strategy for a microscope temperature stage based on thermoelectric elements. The design allows the user to access a range of temperatures below and above room temperature and can accommodate samples of different geometries. In addition, by cooling simultaneously the sample insert and the objective, we minimize the temperature gradients along the sample for large magnification objectives requiring immersion oil. We illustrate how this design can be used to study the physiology of the zebrafish embryo over the temperature tolerance of this species. We envision that this device could benefit the communities using model and non-model organisms with physiological temperatures different from typical mammalian cell culture incubation in biomedical research.